(untitled) (Baghdad Science Journal, 2021)
In recent years, the demand for air travel has increased and many people have traveled by plane. Most passengers, however, feel stressed due to the limited cabin space. In order to make these passengers more comfortable, a personal air-conditioning system for the entire chair is needed. This is because the human body experiences discomfort from localized heating or cooling, and thus, it is necessary to provide appropriate airflow to each part of the body. In this paper, a personal air-conditioning system, which consists of six vertically installed air-conditioning vents, will be proposed. To clarify the setting temperature of each vent, the airflow around the passenger and the operative temperature of each part of the body is investigated using fluid simulation. In the simulation, the ideal temperature for each part of the body is defined and compared with the operative temperature to verify how close both temperatures are, resulting in determining the ideal setting temperature. The simulation result shows, that most parts of the body reach their ideal temperatures. In addition, the optimum setting temperature and position of each air-conditioning vent, which contribute to maintaining the thermal comfort of the human body on the plane, is clarified.